The potential for CO < inf> 2 -induced acidification in freshwater: A great lakes case study - Phillips, Jennifer C.; McKinley, Galen A.; Bennington, Val; Bootsma, Harvey A.; Pilcher, Darren J.; Sterner, Robert W.; Urban, Noel (Oceanography, 2015)
Ocean acidification will likely result in a drop of 0.3–0.4 pH units in the surface ocean by 2100, assuming anthropogenic CO2 emissions continue at the current rate. Impacts of increasing atmospheric pCO2 on pH in freshwater systems have scarcely been addressed. In this study, the Laurentian Great Lakes are used as a case study for the potential for CO2-induced acidification in freshwater systems as well as for assessment of the ability of current water quality monitoring to detect pH trends. If increasing atmospheric pCO2 is the only forcing, pH will decline in the Laurentian Great Lakes at the same rate and magnitude as the surface ocean through 2100. High-resolution numerical models and one high-resolution time series of data illustrate that the pH of the Great Lakes has significant spatio-temporal variability. Because of this variability, data from existing monitoring systems are insufficient to accurately resolve annual mean trends. Significant measurement uncertainty also impedes the ability to assess trends. To elucidate the effects of increasing atmospheric CO2 in the Great Lakes requires pH monitoring by collecting more accurate measurements with greater spatial and temporal coverage.